2018
DOI: 10.1186/s12998-018-0200-4
|View full text |Cite
|
Sign up to set email alerts
|

Be good, communicate, and collaborate: a qualitative analysis of stakeholder perspectives on adding a chiropractor to the multidisciplinary rehabilitation team

Abstract: BackgroundWhile chiropractors are integrating into multidisciplinary settings with increasing frequency, the perceptions of medical providers and patients toward adding chiropractors to existing healthcare teams is not well-understood. This study explored the qualities preferred in a chiropractor by key stakeholders in a neurorehabilitation setting.MethodsThis qualitative analysis was part of a multi-phase, organizational case study designed to evaluate the planned integration of a chiropractor into a multidis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
(65 reference statements)
0
18
0
Order By: Relevance
“…We conducted a longitudinal case study using qualitative methods (interviews, focus groups) as part of a larger research project to evaluate the process and outcomes of adding a DC to the clinical team in a multidisciplinary rehabilitation hospital [ 17 19 ]. The Institutional Review Boards of Palmer College of Chiropractic and Crotched Mountain Foundation provided the research ethics approvals for this project.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We conducted a longitudinal case study using qualitative methods (interviews, focus groups) as part of a larger research project to evaluate the process and outcomes of adding a DC to the clinical team in a multidisciplinary rehabilitation hospital [ 17 19 ]. The Institutional Review Boards of Palmer College of Chiropractic and Crotched Mountain Foundation provided the research ethics approvals for this project.…”
Section: Methodsmentioning
confidence: 99%
“…This report describes stakeholder outcome expectations expressed during baseline interviews conducted before the implementation of the chiropractic program. The methods for this case study are described in greater detail elsewhere [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another example of chiropractors functioning in interprofessional collaboration was provided by Wirth et al who reported on outcomes and trajectories of patients referred from a surgical department to chiropractic care [8]. In these settings, chiropractors frequently work alongside or in collaboration with other providers, and Salsbury et al reported, based on a qualitative stakeholder analysis, that in order to be successful in multidisciplinary teams, chiropractors should be good clinicians, practice according to evidence, be communicative and be supportive of patient's emotional journeys during care and rehabilitation [9]. Four articles dealt with different elements of chiropractic practice.…”
Section: Commentarymentioning
confidence: 99%